A state of the art review on phosphate removal from water by biochars - Ismail W. Almanassra (14151321) (2021)
In the last decade, biochar (BC) has attracted significant attention for the removal of pollutants from aqueous solutions. Biochar exhibits many distinctive characteristics that make it an attractive adsorbent due to its availability, low manufacturing cost and compelling surface properties. This review presents a comprehensive summary of BC’s application in phosphate remediation. Adsorption isotherm, kinetics, experimental conditions and the effect of different adsorption parameters on phosphate removal are outlined. The adsorption mechanisms, effect of coexisting ions, desorption studies and reuse of exhausted BCs are also considered. The results demonstrate that unmodified BCs possess low phosphate sorption capacity with the exception of BCs with high minerals content. As such, engineered BCs by decoration with different elements have been shown to alter the surface characteristics of the adsorbents such as surface charge, surface area, pore diameter, pore volume and the surface functional groups. Therefore, the phosphate sorption capacity of modified BCs has been significantly improved compared to unmodified adsorbents. Magnesium, aluminum, calcium and lanthanum were of significant interests for BC decoration due to their high affinity toward phosphate ions. Iron has been also widely used in BC composites for increasing the adsorption capacity of phosphate, in addition to providing an opportunity for magnetic recovery of the adsorbent. Based on this review, future research for BC applications in terms of phosphate removal is also discussed. Other Information Published in: Chemical Engineering Journal License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cej.2020.128211